2020
DOI: 10.9770/jesi.2020.7.3(27)
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of enterprise resource planning (ERP) implementation in agriculture

Abstract: The underlying assumption of the study is that ERP systems can crucially facilitate information exchange; yet, the agricultural sector is slow in their adoption due to different reasons, including a shortage of skilled personnel as well as a lack of knowledge about ERP capabilities among top managers and key employees. The study intends to identify challenges and prospects for ERP implementation in agriculture. The applied methods include the analysis of WoS publications and questionnaire surveys of executives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Limited knowledge and skills for using ICT by farmers contribute to the challenges (Abdullah, 2015; Mulauzi and Albright, 2008) or in delayed development (Murugesan and Sudarsanam, 2020). Kulikov et al (2020) in their survey found this to be a major issue, especially with respect to the lack of knowledgeable, trained and skilled workers capable of operating digital technologies and systems. This is also supported by the study of Chandra et al (2017), who performed research about climate smart farming.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Limited knowledge and skills for using ICT by farmers contribute to the challenges (Abdullah, 2015; Mulauzi and Albright, 2008) or in delayed development (Murugesan and Sudarsanam, 2020). Kulikov et al (2020) in their survey found this to be a major issue, especially with respect to the lack of knowledgeable, trained and skilled workers capable of operating digital technologies and systems. This is also supported by the study of Chandra et al (2017), who performed research about climate smart farming.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…According to Kulikov et al (2020), the ERP system evolved from Material Requirement Planning (MRP) systems and Manufacturing Resource Planning (MRPII) systems. MRP systems combine manufacturing functions such as purchasing, material, planning, and operations and MRPII systems coordinate manufacturing activities with other functional areas such as marketing, finance, and engineering.…”
Section: Enterprise Resource Planning Systemmentioning
confidence: 99%
“…Resource Module, Supply Chain and Distribution Module, Procurement Management Module, and Manufacturing Module (Gopaul, 2016). From a technical perspective, an ERP system comprises of modules usually intended to serve various organisations through a consolidated database (Kulikov et al, 2020). According to Bukamal and Wadi (2016), an ERP system has an outstanding ability to simplify business transactions, reduce non-value-added activities, and improve customer services; therefore, the system is popular and successful.…”
Section: Enterprise Resource Planning Systemmentioning
confidence: 99%
See 2 more Smart Citations